STUDI BIBLIKA KORELASI TEOLOGI PAULUS DAN TEOLOGI YAKOBUS TENTANG IMAN DAN PERBUATAN IMAN - Gidion, Gidion (Shift Key : Jurnal Teologi dan Pelayanan, 2018)
There are diverse views within the Christian group about faith and works. Sproul and the Evangelical group with full conviction that the â€œworksâ€is the fruit or sign of faith. But Peter David and the Pentecostal group have the view that faith together with works produce perfect faith. What Paul and James teach salvation by faith or by works? Or salvation by faith + works? Is it true that the faithful do not care about their moral good or bad? The differences in views between Paul and James about faith and works, some later concluded that there were quarrels in these two figures. This problem then became an important issue to be discussed, because in the history of the church, Martin Luther gave the conclusion that the views of Paul and James about faith and works were indeed contradictory.